DAMPAK PENAMBANGAN BAHAN GALIAN C TERHADAP LAHAN DI BATANG KALUMBUK KENAGARIAN AMPANG KURANJI KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Putri, Adisa - (Pendidikan Geografi, 2014)
This study aims to find out about the impact of the Mining Minerals C on Land In KenagarianDistrict of Koto Baru Ampang Kuranji Dharmasraya, in terms of: (1) Widening of the river due to miningof minerals category C to the land. (2) Erosion of riverbanks due to mining of minerals category C to theland.The method used is descriptive quantitative method. The sampling method using purposive sampling, inwhich the measurement is done along the river Batang Kalumbuk. Widening of the river and river bankerosion by river flow velocity, slope, vegetation cover and rock outcrops.The results showed that: (1) there has been a widening Kalumbuk rod which varies between 7 - 12m, in sample 1 is the widening of the river reaches 7 meters, the second sample dilation reaches 8 metersand the sample 3 had 12m width. (2) The flow rate in the study area varies later than 56.03 cm / sec andthe fastest 62.35 cm / sec. encourage the flow velocity of the river bank erosion. (3) The slope of the slopeof the study area including the class II category ramps. (4) Vegetation land cover classified as class II(Low) closure vegetation consists of grasses, plantations, coconut, oil palm, rubber bushes and plants. (5)The rate of river bank erosion by rock outcrops in the study area belong to the class II (Low), namely:between 2 - 10% and 10 - 50%